Avaliação espacial dos níveis de mercúrio total em sedimentos do reservatório da UHE de Curuá-Una, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Hydroelectric uses in the Amazon promote, in most cases, the inundation of extensive forested areas, which may stimulate the mobilization of the mercury naturally present in these soils. Reservoir sediments act as mercury receptors from upstream drainage, providing conditions conducive to bioavailability of the most toxic form of the metal, methylmercury. This work was carried out during the month of November of 2016 and had the objective of spatially evaluating the levels of total mercury (HgT) in background (SF) and suspended (SS) sediments and to relate them to limnological variables. In order to do this, 17 points distributed along the longitudinal gradient of the aquatic system of the Curuá-Una HPP were grouped into four regions: fluvial upstream (rivers: Curuá-Una, Moju and Mojuí), transition, lacustrine and fluvial downstream. In these, the SF was extracted in profiles of 30 cm depth and subdivided in layers of 2 cm each, by means of the KAJAK vertical core type sediment collector, and the SS were collected in punctual samplings in the water column together with measurements of the physical-chemical variables of water. After sampling, the sediments were greenhouse dehydrated, granulometrically fractionated in sieves and fine sediment samples, as well as filters containing suspended sediment mass analyzed by Cold Steam Atomic Fluorescence Spectrometry for determination of HgT. Thus, concentrations differed significantly between the four regions assessed with an increase in mean HgT levels from the upstream fluvial region (185.4 ± 23.6 ng.g -1 ), transition (222.9 ± 63.1 ng.g-1 ) for the lacustrine (263.3 ± 33.6 ng.g-1 ) with decay in the downstream fluvial region (156.6 ± 24.6 ng.g-1 ). As for the vertical distribution of the concentrations of total Hg in the sediment layers from 0 to 30 cm, most of the regions showed an increase in the base to the top of the tide, mainly in the upstream and lacustrine fluvial regions, as in SF, (385.0 ± 42.23 ng.g-1 ) to the transitional layer (411.9 ± 61.87 ng.g-1 ) , With decay in the lacustrine region (270.3 ± 59.14 ng.g-1 ) and downstream fluvial (177.5 ± 48.17 ng.g-1 ). It was not verified the existence of significant vertical variation of the HgT levels in the profiles of the water column in the lacustrine region. There was interaction of the limnological variables with the concentrations of HgT in the two sediment matrices. Thus, regions of the aquatic system with low values of pH (acid waters), electrical conductivity, concentration of suspended sediments and high values of organic matter in the bed, provide sites with higher values of total mercury in the bottom sediments. Already regions with low pH, high color, turbid and colder water contribute to higher values of HgT in suspended sediments. Thus, it is inferred that part of the HgT associated to sediments suspended in the hydrosystem of the Curuá-Una HPP, which originates from the anthropogenic drainage area of the forming rivers, is retained in the lake region (57%) and part is exported (43 %) By the turbination of the waters of the hypolimnium, remaining with constant concentrations along the next 15 km downstream.
Keywords: Rio Mojuí; Hidrossistema; Lacustre; Ecotoxicologia; Amazônia; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO